STRATEGI BAURAN PEMASARAN DALAM MENINGKATKAN TINGKAT HUNIAN KAMAR PADA GLAMPING DI TAMAN DANU CAMP, BEDUGUL - Fachlepi, Imam; Sudiarta, I Nyoman; Sendra, I Made (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023)DO - 10.24843/IPTA.2023.v11.i02.p13, 2023)
Glamping activities have become one of the trends in the world of tourism, making many tourism industry managers compete in fulfilling this trend. Taman Danu Camp is one of the Glamping areas in Bedugul. The existence of this competition makes Taman Danu Canp have to maximize marketing strategies to increase sales of Glamping rooms. This study used data collection techniques, namely observation, library studies, questionnaires, interviews, and distributing questionnaires to obtain data. The results showed that the marketing strategy at Taman Danu Camp, SO (strength Opportunity) Strategy: strategies to increase and maintain excellence and strategies to expand market share. WO (weakness opportunity) strategy: a strategy to improve product quality and a strategy to improve service quality to tourists. ST strategy (strength threats): strategies to maintain a positive image of Glamping both in the community and in the perception of tourists and strategies to expand cooperation. WT (weakness threats) strategy: strategies to improve the quality of products and services and strategies to improve the quality of resources.